2015
DOI: 10.1002/trtr.1397
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Quality of Think-Alouds

Abstract: The power of effective teacher-generated think-alouds is indisputable. However, teachers often struggle to plan and implement think-alouds in routine classroom instruction. This article breaks down the process of planning effective think-alouds into three easy-to-follow steps.There are many steps between knowing what an effective teaching strategy is and knowing how to do it. The more I prepared and tried out think-alouds, the more confident I became in my knowledge that this was something I both should do and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
0
15
0
1
Order By: Relevance
“…Cada participante realiza la verbalización durante entre 40 y 50 minutos en la oficina de la universidad, lugar libre de molestia externa. Esa verbalización introspectiva viene haciéndose el paradigma preferente para acceder a la "caja negra" de la mente humana (Ashraf, Yazdi y Samir, 2017;Ness y Kenny, 2016;Caldwell y Leslie, 2010;Block e Israel, 2004). Tomamos a estos 15 participantes como procesadores de información conscientes, que hagan una mediación consciente de su comprensión y verbalicen de manera simultánea los procesos y estrategias cognitivos.…”
Section: Metodologíaunclassified
“…Cada participante realiza la verbalización durante entre 40 y 50 minutos en la oficina de la universidad, lugar libre de molestia externa. Esa verbalización introspectiva viene haciéndose el paradigma preferente para acceder a la "caja negra" de la mente humana (Ashraf, Yazdi y Samir, 2017;Ness y Kenny, 2016;Caldwell y Leslie, 2010;Block e Israel, 2004). Tomamos a estos 15 participantes como procesadores de información conscientes, que hagan una mediación consciente de su comprensión y verbalicen de manera simultánea los procesos y estrategias cognitivos.…”
Section: Metodologíaunclassified
“…When students needed to be introduced to new or challenging concepts or appeared to be unsure of learning points during active demonstrating, teachers used "think alouds" to demonstrate the concept or point (Ness & Kenny, 2016). While the teacher articulated an inner dialogue about how to solve a writing problem (such as selecting the most appropriate detail or word in a text), students watched and listened in order to be able to transfer the demonstrated skill to their own writing.…”
Section: Effective Teachers Demonstrate Learning Processesmentioning
confidence: 99%
“…We found that a highly scaffolded read-aloud / think-aloud process (e.g., Ness & Kenny, 2016) was very helpful when we introduced the strategy to our grade 1 classes. We modeled the use of the strategy repeatedly using very simple informational texts, and we then guided students through other simple informational texts.…”
Section: Introducing the Strategy To Beginning Readersmentioning
confidence: 97%